The Dark Side of Enchantment - Vaz da Silva, Francisco (16th Congress of the International Society for Folk Narrative Research, 2013)
This paper examines the distinctive traits of enchantment in traditional wondertales (ATU 300–749). Since a spell of enchantment—a reversible death-like state, akin to the liminal stage in rites de passage—is usually active at the core of wondertale plots, a stroll by forest huts and dragon caves offers close-up glimpses of that dark phase. During enchantment, characters take on paradoxical traits, they undergo metamorphosis, and they repair to dark netherworld realms. Enchanted characters often turn into birds or they take animal shapes, being effectively assimilated to wandering souls (recall that “animal” > anima, soul). And, crucially, they tend to shed blood and to be caught in blood (kin) relations. This paper examines the symbolic codes that depict these liminal states; it asks how the complex ontology of enchantment relates to the many-worlds topography of wondertales; and it seeks to understand how enchantment relates to traditional ideas about death, the flight of the soul, and rebirth.